Competitive Advantage as Mediating Factor for Creating Firm Value: A Literature Review - Andes, Septa Lukman; Nuzula, Nila Firdausi; Worokinasih, Saparila (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2020)
This study aims to examine previous research to determine the role of competitive advantage as a variable mediating the effect of corporate governance and intellectual capital on firm value. This study applies theories namely agency theory, bargaining power theory, tokenism theory, market orientation theory, managerial rents theory, and dynamic capabilities theory to explain the relationships between variables. As a literature review, this article contributes to developing a conceptual framework by combining two different perspectives of governance and intellectual capital management, namely shareholder and stakeholder perspectives. This paper has important implications for management and future research as not many previous studies have used the theoretical framework to test the research model. This study has limitations in obtaining research that examines the influence of competitive advantage on firm value. Nevertheless, this study carries a new framework that illustrates the contribution of competitive advantage to firm value through the application of the principles of corporate governance and management of intellectual capital.